Sosialisasi Model Pembelajaran Pola Gerak Dominan pada Materi Senam Ketangkasan bagi Guru PJOK di Kecamatan Kwandang Kab. Gorontalo Utara - Zulkifli Lamusu; Muhamad Reza Pratama Diuli; Sarjan Mile (Universitas Negeri Gorontalo, 2026)
Gymnastics learning in elementary schools often encounters several challenges, particularly students’ lack of confidence in performing gymnastic movements and teachers’ limited ability to implement innovative instructional models. This community service program aimed to enhance the knowledge and skills of Physical Education, Sports, and Health (PJOK) teachers in applying the Dominant Movement Pattern (DMP) learning model to gymnastics instruction. The program involved 25 elementary school PJOK teachers in Kwandang District, North Gorontalo Regency, and was conducted using a participatory approach through lectures, discussions, simulations, and hands-on practice. Program evaluation was carried out using satisfaction questionnaires and pre- and post-activity assessments. The results indicated a high level of participant engagement, with a 92% satisfaction rate categorized as excellent. Evaluation findings further revealed that 88% of participants demonstrated a good understanding of the concepts and application of dominant movement patterns in gymnastics instruction, increasing from 64% before the program to 88% after participation, representing a 24% improvement in understanding. In addition, participants gained practical experience in designing safe, enjoyable, and developmentally appropriate learning activities for elementary school students. The program positively contributed to improving teachers’ pedagogical competence and creativity in developing gymnastics learning based on dominant movement patterns. Therefore, this socialization program proved effective in enhancing teachers’ understanding and readiness to implement more innovative and student-centered physical education instruction.